Engaging in energy: Typology of urban young entrepreneurs in shaping Nepal’s double energy transition - Quaresima,Giuliana; Mørup Sønnichsen,Freja (Master Thesis Series in Environmental Studies and Sustainability Science, 2025)
Nepal is in the midst of a double energy transition aiming to improve energy reliability whilst simultaneously increasing renewables. We consider to what degree and in which ways young entrepreneurs contribute in shaping Nepal's transitory landscape as a group with social power. To assess this, we developed the Participation in Energy Transitions (PET) framework integrating Energy- Literacy and Citizenship theory. We identify a typology of engagement in the energy transition; “Not engaging”, “Discussing without advocacy”, “Aware, but disempowered”, “Unaware, but engaged” and finally “Leading with action and advocacy”. We also identify entrepreneurs' engagements with the energy transition as dominated by informal-, and formal advocacy accompanied by some material participation. Finally, we consider the opportunities and obstacles for engagement from structural, normative, economic and cognitive perspectives. To incentivize entrepreneurial engagements, we recommend increasing awareness of renewable energy, introducing energy engagement opportunities in collective settings, strengthening entrepreneurial culture and tailoring policy incentives.
Keywords: Sustainability Science; Energy Transition; Energy Citizenship; Entrepreneurs; Nepal